2022
DOI: 10.1186/s12916-022-02679-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel proteins underlying schizophrenia via integrating pQTLs of the plasma, CSF, and brain with GWAS summary data

Abstract: Background Schizophrenia (SCZ) is a chronic and severe mental illness with no cure so far. Mendelian randomization (MR) is a genetic method widely used to explore etiologies of complex traits. In the current study, we aimed to identify novel proteins underlying SCZ with a systematic analytical approach. Methods We integrated protein quantitative trait loci (pQTLs) of the brain, cerebrospinal fluid (CSF), and plasma with the latest and largest SCZ g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…The strength of MR association p-values is represented by a blue gradient across data values. The strength of association is further annotated for easy reference, nominally significant p < 0.05 (circle), FDR significant p scz < 1.49 x 10 - 4 , p BIP < 2.07 x 10 - 5 p MDD < 1.55 x 10 9 p CTP < 2 x 10 - 7 (square) and Bonferroni significant p < 7.34 x 10 - 6 (triangle) are annotated accordingly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength of MR association p-values is represented by a blue gradient across data values. The strength of association is further annotated for easy reference, nominally significant p < 0.05 (circle), FDR significant p scz < 1.49 x 10 - 4 , p BIP < 2.07 x 10 - 5 p MDD < 1.55 x 10 9 p CTP < 2 x 10 - 7 (square) and Bonferroni significant p < 7.34 x 10 - 6 (triangle) are annotated accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Genomewide association studies (GWAS) represent a high-throughput, comprehensive, and unbiased tool in providing insights into psychopathology; however, in-depth mechanistic insights that contribute to the disorders' pathogenesis might be further elucidated by leveraging additional functional data. The growing utilization of high-throughput proteomics platforms in large-scale genotyped biobanks provides new opportunities to obtain biological insights from GWAS data [7][8][9][10] . Notably, the Mendelian Randomization (MR) approach 11 permits the identification of causal mechanisms, avoiding the potentially confounding effects of environmental exposures while allowing for sample sizes that are orders of magnitude larger than conventional case-control reports.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsin S also plays a role in regulating the integrity of the blood–brain barrier (BBB), and changes in BBB permeability may affect the entry of immune cells and inflammatory factors into the brain, potentially contributing to the onset of psychiatric disorders [ 72 ]. Recent genetic studies have found potential associations between the CTSS gene and susceptibility to schizophrenia [ 73 ]. However, it's crucial to note that the relationship between CTSS and psychiatric disorders, especially schizophrenia, is complex and multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Among these proteins, CNTN2, APBA1, and APBA2 acquire a distinct interest due to their observed involvement in various molecular and clinical conditions . In particular, CNTN2 would certainly deserve further investigations since it has been demonstrated to be implicated in various neurodevelopmental processes , and psychiatric conditions, , which could have indeed a major pathogenetic relevance for blast-TBI related syndromes and PTSD in particular.…”
Section: Discussionmentioning
confidence: 99%